The Implementation of Islamic Education Values by Islamic Religious Education Teachers as a Preventive Effort Against Student Delinquency at SMKN 1 Abung Selatan. - Eka Nurdayanti Fadillah; Dedi Setiawan; M. Sayyidul Abrori (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to describe the implementation of Islamic educational values by Islamic Religious Education (PAI) teachers as a preventive effort against student delinquency at SMKN 1 Abung Selatan. The background of this research is the continued presence of students’ indisciplinary behaviors, such as tardiness, violations of school rules, the use of mobile phones during lessons, and low participation in religious activities. This study employs a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. Data analysis is conducted through data reduction, data display, and conclusion drawing, with validity tested through source and technique triangulation. The results of the study indicate that the implementation of Islamic educational values is carried out through three stages: planning, implementation, and evaluation, all oriented toward prevention. Teachers integrate values such as discipline, responsibility, honesty, and moral conduct (akhlaq) into both learning processes and religious habituation activities. The implementation is conducted through role modeling, persuasive advice, enforcement of discipline, and routine religious activities. Evaluation is carried out by monitoring changes in students’ behavior, which are indicated by a decrease in tardiness and rule violations, as well as increased participation in religious activities. This implementation serves as an effective preventive effort in reducing student delinquency at mild to moderate levels, thereby creating a more conducive and orderly school environment